2006
DOI: 10.2337/dc05-2565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calorie Restriction With or Without Exercise on Insulin Sensitivity, β-Cell Function, Fat Cell Size, and Ectopic Lipid in Overweight Subjects

Abstract: THE PENNINGTON CALERIE TEAMOBJECTIVE -The purpose of this article was to determine the relationships among total body fat, visceral adipose tissue (VAT), fat cell size (FCS), ectopic fat deposition in liver (intrahepatic lipid [IHL]) and muscle (intramyocellular lipid [IMCL]), and insulin sensitivity index (S i ) in healthy overweight, glucose-tolerant subjects and the effects of calorie restriction by diet alone or in conjunction with exercise on these variables. RESEARCH DESIGN AND METHODS-Forty-eight overwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
338
4
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(391 citation statements)
references
References 52 publications
33
338
4
10
Order By: Relevance
“…The number of men and women was not reported for 3% of the subjects. These studies investigated a wide range of weight-loss interventions including caloric restriction, 9,11,13,14,16,17,19,[20][21][22][23] 10,18,24 One study reported data from women with type 2 diabetes 17 and another study investigated HIV-positive women. 15 We plotted the loss of visceral fat mass relative to the total loss of fat mass (DVAT/DFM) against the initial visceral fat mass divided by the total fat mass (VAT/FM).…”
Section: Resultsmentioning
confidence: 99%
“…The number of men and women was not reported for 3% of the subjects. These studies investigated a wide range of weight-loss interventions including caloric restriction, 9,11,13,14,16,17,19,[20][21][22][23] 10,18,24 One study reported data from women with type 2 diabetes 17 and another study investigated HIV-positive women. 15 We plotted the loss of visceral fat mass relative to the total loss of fat mass (DVAT/DFM) against the initial visceral fat mass divided by the total fat mass (VAT/FM).…”
Section: Resultsmentioning
confidence: 99%
“…The results from these studies using a variety of interventions, either by diet alone 81,83,84,89,92,93 or in combination with different exercise prescriptions, 82,[85][86][87][88]92,94 have consistently reported a significant reduction in liver fat by an average of $40% (ranging from 20% to 81%). The degree of hepatic fat reduction was proportional to the intensity of the lifestyle intervention and generally required a body weight loss between $5 to 10%.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…However, what is unequivocal is that DR induces significant health benefits in many animals, and arguably what is really important is a greater period of total life free from age-related disease rather than an extension of lifespan per se. In human subjects, it is evident that even shortterm and relatively moderate DR in overweight and obese individuals, and in non-obese individuals, can confer a multitude of health benefits (75)(76)(77)(78) . For example, DR appears to protect against a range of age-related diseases in human subjects, including obesity, CVD, arteriosclerosis and hypertension (75)(76)(77)(78)(79)(80)(81) .…”
Section: Is Dietary Restriction a Realistic Intervention Inmentioning
confidence: 99%
“…In human subjects, it is evident that even shortterm and relatively moderate DR in overweight and obese individuals, and in non-obese individuals, can confer a multitude of health benefits (75)(76)(77)(78) . For example, DR appears to protect against a range of age-related diseases in human subjects, including obesity, CVD, arteriosclerosis and hypertension (75)(76)(77)(78)(79)(80)(81) . DR also slows age-related declines in left ventricular diastolic function, increases insulin sensitivity and reduces the levels of several inflammatory cytokines (75) .…”
Section: Is Dietary Restriction a Realistic Intervention Inmentioning
confidence: 99%